Internet of Things Based Electricity Monitoring System for Rural Distribution Networks - Husainy, Muhamad Fakhrul Amri; Ahmad, Afandi; Mohd Nadzri, Muhammad Muzakkir (Evolution in Electrical and Electronic Engineering, 2021)
Electricity is essential in our daily lives and has an impact on economic and social development. This project aims to solve the incapability to monitor the absence of electricity in rural areas as it is out of coverage in terms of telecommunication. The proposed solution allowing the electrical energy operator/manager to monitor the absence of electricity and immediate action can be taken to restore the electricity. This prototype is an Internet of Things (IoT) monitoring system that perform long-range data transfer by utilising advanced        low-power, wide-area network (LoRaWAN), sensor nodes that utilised the current sensor to detect the absence of electricity, NodeMCU ESP8266 as a gateway equipped with Wireless Fidelity (Wi-Fi), Microsoft Azure cloud storage and                     Microsoft Power BI for graphical user interface (GUI). Results obtained show that the prototype has the ability to transfer the data up to 150 meter with the battery lifetime sustain for 13 hours. Hence, it proves that this prototype can be further expanded for real implementation in rural areas.